Problemy wzrostu dochodów ludności i konsumpcji w Związku Radzieckim - Piasny, Janusz (Wydział Prawa i Administracji UAM, 1969)
In the paper there are represented some indices of the changes of the living standard of people, who live as well in the town as in the country. The basical indices were worked out mainly in reference to the years 1950 -1967, only in some cases there were shown the general tendencies that took place in the scope of income and consumption in the last 50 years. A steady base of the growth of income of people as well direct as indirect Was the increase of the national income that in the course of the last 50 years multiplied 37 times. In the consequence the real income of workers, who worked in the industry and building increased 5 times per 1 worker and the real income of people increased above 9 times. The growth of real people's income was done mainly in 3 ways, namely as the result of the successive reduction of pricess for some goods of common comsumption, by the increase of workers wages and the steady enlarging of the social services from the social funds of consumption. In the result of the increase of real income there was changed not only the amount of consumption but also the structure of the consumption of the Soviet people. In the scope of consumption of food there increased especially the consumption of meat, fish, fish products, milk, diary products, eggs and vegetables. The tendency of improving the quality of the eaten products was very distinct especially in the last 17 years. In the examined period of time (1950 -1967) there increased many times shopping of the articles of culture-existential goods. A big dynamics was shown in buying television sets, radio sets, furniture, bicycles, motorcycles, scooters, refrigerators, electric cleaners, polish machines, sewing machines, and all kinds of tricots, clothes and shoes., A big influence on the improving of living conditions and on the structure of people's expenses had in the last years an immense development of the residential building. In the result of big progress in the residential building in the last 12 years almost 160 millions of Soviet citizens improved their living conditions. The people of the Union of Soviet Socialist Republics increased their savings with every year. In 1967 the whole amount of the reached 27 milliards roubles. These savings have been saved mainly for buying private cars and furniture
Problems of Growth of Income and Consumption of the Population in the USSR